Biofilm adhesion on polypropylene and nylon sutures in clinical crown lengthening surgery: controlled clinical trial - Ana Carolina Zorrilla Mattos; Angel Steven Asmat-Abanto (Amaltea Medical Publishing House, 2024)
Objective. The aim of this study was to compare biofilm adherence in polypropylene versus nylon sutures in clinical crown lengthening surgery on anterior teeth. Material and methods. This controlled clinical trial was conducted in 2019 at the Dental Center and the Microbiology Laboratory of the "Antenor Orrego" Private University, with 30 patients undergoing clinical crown lengthening surgery for prosthetic reasons of an anterior tooth who met the established selection criteria. Participants were chosen using the non-probabilistic selection method, and the reliability was determined by calibration using an intra-evaluator (0.984) and an inter-evaluator (0.978) with an independent collaborator. The bacterial adhesion of polypropylene and nylon threads was compared seven days after surgery using the paired-sample Student's t-test and also compared to a control. A significance level of 5% was considered. Results. Initially, there were 37 patients, of whom 7 were eliminated because they lost their suture threads. There is a significant difference (p=0.001) between the adherence of biofilm in polypropylene sutures compared to nylon after clinical crown lengthening surgery. Conclusion. Polypropylene suture adheres less biofilm compared to nylon in clinical crown lengthening surgery.